Freedom is a bridge, not a highway (Alternate Horizons, 2024)
In the build-up to the South African election season, 'freedom' emerges as a hot topic. There is much talk of 'freedom' from social and economic injustice from aspiring presidents; a lot of reminiscing about what 30 years of 'freedom' has secured for a segregated country; many debates about who deserves to lead South Africa in the next 30 years of 'freedom'. Yet in all this talk about 'freedom', the term is rarely defined by those with promises to advance it and the concept is seldom examined in the context of 21st century South Africa. In many cases, politicians seem to use the ideas of 'freedom' and 'liberty' interchangeably. In an attempt to make sense of a term that we wield far too frequently, this paper is concerned with the concept of freedom and its presence in South Africa in the 21st century. The paper discusses the manifestations of freedom and liberty in contemporary society and the social responsibility of South Africans to engage with it, not as the final destination, but as a vehicle to a final destination.
Keywords: Democracy; freedom; ubuntu; South Africa; transition; Voting